Biological Apexogenesis of Undeveloped Tooth in a Patient with Spondyloepiphyseal Dysplasia: A Case Report - Ashraf, Hengameh; Eskandarinezhad, Mahsa (Iranian Endodontic Journal, 2010)
This case report describes treatment of a necrotic immature permanent mandibular first molar with pulpal necrosis in 9-year old female with spondyloepiphyseal dysplasia. The coronal half of the root canal was debrided with a file #30 to remove necrotic tissue, and irrigated with chlorhexidine 0.12%. Bleeding was evoked to form an intracanal blood clot; the wound was then dressed with calcium hydroxide medication and provisionally restored with GIC. This was repeated at intervals of 1, 3 and 6 months. After six months, radiographic evidence revealed thickening of dentinal walls and apical closure. The progressive increase in dentinal wall thickness and apical development suggests that desirable biologic responses can occur with this form of treatment for the necrotic open apex of immature permanent teeth.